(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article describes the conditions for the formation of the competences of the professional-methodical training of the future art teacher, and the stages of development of the level of student mastery. For this purpose, the school art teacher should first of all improve his professional creativity and motivational abilities, his role in the teaching of school art, the essence of his place, and then the didactics of teaching school art. It is necessary to get to know its principles and teaching methods well, and learn when, where, and in what context to use them.